Effectiveness of Some Vitamins in the Prevention of Cardiovascular Disease: A Narrative Review - Shah, Anureet K.; Dhalla, Naranjan S. (Frontiers in Physiology, 2021)
By virtue of their regulatory role in various metabolic and biosynthetic pathways for energy status and cellular integrity, both water-soluble and fat-soluble vitamins are considered to be involved in maintaining cardiovascular function in health and disease. Deficiency of some vitamins such as vitamin A, B6, folic acid, C, D, and E has been shown to be associated with cardiovascular abnormalities whereas supplementation with these vitamins has been claimed to reduce cardiovascular risk for hypertension, atherosclerosis, myocardial ischemia, arrhythmias and heart failure. However, the data from several experimental and clinical studies for the pathogenesis of cardiovascular disease due to vitamin deficiency as well as therapy due to different vitamins are conflicting. In this article, we have attempted to review the existing literature on the role of different vitamins in cardiovascular disease with respect to their deficiency and supplementation in addition to examining some issues regarding their involvement in heart disease. Although both epidemiological and observational studies have shown some merit in the use of different antioxidant vitamins for the treatment of cardiovascular disorders, the results are not conclusive. Furthermore, in view of the complexities in the mechanisms of different cardiovascular disorders, no apparent involvement of any particular vitamin was seen in any specific cardiovascular disease. On the other hand, we have provided evidence that deficiency of vitamin B6 promoted KCl-induced Ca2+ entry and reduced ATP-induced Ca2+-entry in cardiomyocytes in addition to decreasing sarcolemmal (SL) ATP binding. The active metabolite of vitamin B6, pyridoxal 5'-phosphate, attenuated arrhythmias due to myocardial infarction (MI) as well as cardiac dysfunction and defects in the sarcoplasmic reticulum (SR) Ca2+-transport in the ischemic-reperfused hearts. These observations indicate that both deficiency of some vitamins as well as pretreatments with different vitamins showing antioxidant activity affect cardiac function, metabolism and cation transport, and support the view that antioxidant vitamins or their metabolites may be involved in the prevention rather than the therapy of cardiovascular disease.